"The sky over Kharkiv": on the political and imagological functions of translation - Ivanytska, Maria (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
The aim of the research is to highlight two specific functions of translation, namely political and imagological, based on Ukrainian-German translation over the past three years. The study is relevant because of the need to demonstrate the importance of translation in the political arena, primarily in creating an image of Ukraine, its literature and culture abroad. The object of the study is the impact of translation on the formation of public opinion in Germany about Ukraine and its literature, and the subject of the study is the verbalisation of the imagological function of translation in all its manifestations. The research is based on the book by Serhiy Zhadan “Himmel über Charkiw. Nachrichten vom Überleben im Krieg” (2022) published in Germany, reviews of the book, and public discussions about the author and Ukrainian literature in the German-language press and social media. The main results of the study: the book is characterised as a translation without the original text; the role of translation field agents in preparing the publication and ensuring its reception in the German-speaking literary scene is described; the reviews and the feedback on the publication as well as the frequency of lexemes in them are analysed and the results are visualised in a word cloud; translation approaches are described. Conclusions: The book “Himmel über Charkiw” is a creative intermedial translation product that holds a key role in the socio-political and literary space of Germany thanks to the cooperation of translation field agents with solid linguistic, educational and symbolic capital and the active position of intercultural mediators and promoters of Ukraine: the author, the translators, the publishers and the experts. The book fulfilled an important political and imagological function, offering a multi-vector positive image of Ukrainian society defending its independence and cultural achievements, and appealing to the German-speaking audience to support Ukraine. The discussions around the book increased its media presence and focused on a number of political, aesthetic, cultural and emotional aspects that sensitised the reader to the perception of Ukraine. This research was supported by a grant from the MSCA4Ukraine project, which is funded by the European Union.